Genetic Diversity and Phylogenetic of Longtail Tuna (Thunnus tonggol) Landed in Pabean Fish Market, Surabaya - Ida Ayu Astarini; Shella Ayu Ardiana; I Nyoman Giri Putra; Putu Dian Pertiwi; Andrianus Sembiring; Astria Yusmalinda; Danie Al Malik (Musamus Fisheries and Marine Journal, 2021)
Indonesia is the biggest tuna exporter in Southeast Asia. With a high number of tuna catch, it is worried that the catch will decrease tuna population, specifically longtail tuna. To anticipate the decrease, there needs to be a conservation program to protect longtail tunas from scarcity. One method used to protect longtail tuna is by genetic conservation. The aim of this research is to understand the genetic and phylogenetic variety of the longtail tuna in Pabean Surabaya Fish Market. The polymerase chain reaction was used to amplify segment of the mitochondrial control region gene from members of these sample, used forward primer CRK 5’-AGCTC AGCGC CAGAG CGCCG GTCTT GTAAA-3’ and reverse primer CRE 5’-CCTGA AGTAG GAACC AGATG-3’. Based on the sequencing process, 28 out of 29 samples longtail tuna were analyzed successfully. The results of the 28 sample analysis of longtail tuna based on its genetic variety and phylogenetic tree reconstruction showed a haplotype variety (Hd) score of 1,00000, and nucleotide (π) variety of 0,1939. Genetic variety value showed that longtail tuna has great adaption capabilities toward environmental changes time to time. Phylogenetic tree reconstruction results showed 7 clades with a genetic range of 0,005 – 0,035, which shows that all samples are closely related. The results of this study can be used as basic information in forming regulations on longtail tuna sustainable management and genetic conservation.